2016
DOI: 10.1016/j.ijedudev.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The impact of effective teaching characteristics in promoting student achievement in Ghana

Abstract: This paper investigates the extent to which teacher behaviour in classroom affects student achievement gains in mathematics in Ghana. A representative sample of primary schools from three districts of the Upper East Region of Ghana was selected (n = 73) using stage sampling procedure, and written tests in mathematics were administered to all grade six students at the beginning and end of school year 2013-2014. Two observation instruments and a student questionnaire were used in collecting data on quality of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 38 publications
3
17
0
2
Order By: Relevance
“…The assumption is that teachers with high academic and professional qualifications will lead to improved student attainment (Organisation for Economic Co-operation and Development, 2012; World Bank, 2018). However, existing literature from the Ghana context on the effect of these teacher factors on students' attainment is scarce, and results from the small number of studies we uncovered were mixed (e.g., Chowa et al, 2015;Azigwe et al, 2016). For instance, Chowa et al (2015) found no association between the proportion of teachers with post-secondary qualifications and children's educational attainment.…”
Section: Context Of the Studymentioning
confidence: 74%
See 3 more Smart Citations
“…The assumption is that teachers with high academic and professional qualifications will lead to improved student attainment (Organisation for Economic Co-operation and Development, 2012; World Bank, 2018). However, existing literature from the Ghana context on the effect of these teacher factors on students' attainment is scarce, and results from the small number of studies we uncovered were mixed (e.g., Chowa et al, 2015;Azigwe et al, 2016). For instance, Chowa et al (2015) found no association between the proportion of teachers with post-secondary qualifications and children's educational attainment.…”
Section: Context Of the Studymentioning
confidence: 74%
“…However, there is little consensus about the specific teacher qualities that lead to greater pupils' learning (e.g., Wayne and Youngs, 2003;Hattie, 2009;Burroughs et al, 2019). Additionally, teacher characteristics can be examined at macro or micro levels, with macro level factors focusing on teacher credentials, while micro factors focus on teachers' behavior within the context of the classroom (Azigwe et al, 2016). In this study, we take advantage of the availability of unique administrative datasets in Ghana to explore the association between teachers' macro level characteristics and children's educational attainment.…”
Section: Teacher Academic Qualification Professional Background Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, literature abounds with research on how different learning activities can be more effective than others. Multilevel analyses show that teacher's factors such as behavior are associated with student learning outcomes [3]. For example, it has been proved that teacher' significant life experiences and stories provide key resources for effective education programs [4].…”
Section: Introductionmentioning
confidence: 99%